THE INFLUENCE OF CAREER SUCCESS ON EMPLOYEE PERFORMANCE TROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT CONVENTIONAL STATE-OWNED BANKS IN THE BEKASI AREA - Agrasadya, Agrasadya; Notosudjono, Didik; Yusnita, Nancy (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to the influence of career success on employee performance through job satisfaction as an intervening variable. This study was conducted using a quantitative approach. The results showed that career success has a significant positive effect on performance, which can be interpreted that the career success variable has a positive effect on performance variables or it can be said that the higher the career success, the higher the performance, conversely the lower the career success, the lower the performance. Job satisfaction has a significant positive effect on performance, which can be interpreted that the job satisfaction variable has a positive effect on performance variables or it can be said that the higher the job satisfaction, the higher the performance, conversely the lower the job satisfaction, the lower the performance. Career success has a significant positive effect on job satisfaction, which can be interpreted that the career success variable has a positive effect on job satisfaction variables or it can be said that the higher the career success, the higher the job satisfaction, conversely the lower the career success, the lower the job satisfaction. Career success has a significant effect on performance that is positively mediated by job satisfaction.